Graduand Student Attributes: A Canadian Case - Kanuka, Heather; Cowley, Summer (Canadian Journal of Higher Education, 2017)
The purpose of this qualitative case study was to gain insights into how academics understand undergraduate graduand attributes. The findings reveal some alignment in views about student attributes, including that they are engaged citizens, are self-directed, have imagination, are questioning, are flexible, display leadership, are problem solvers, and possess character. This consistency, however, does not include the spectrum of views on how these attributes are conceived and developed. The findings reveal a range of interpretations regarding the kinds and levels of understandings of how graduand student attributes are developed throughout an undergraduate program of study. The findings indicate that (i) a shared understanding does not exist on how academics construe student attributes, (ii) academics do not share common meanings about the core achievements of a higher education, or how these are developed through students’ undergraduate programs, and (iii) student attributes tend not to be perceived as developing from the usual process of an undergraduate education.